2001
DOI: 10.1095/biolreprod65.4.1029
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of the Contractile Prostaglandin F Receptor in Pregnant Rat Myometrium in Late Gestation, Labor, and Postpartum1

Abstract: A polyclonal antibody was raised against amino acids 7-18 in the first extracellular loop of rat prostaglandin F (FP) receptor to monitor expression and localization in pregnant rat myometrium at Gestational Days 16, 18, 20, 21, 21.5, 22 (delivery), and 23 (1-day postpartum; n = 5 per group). The antibody recognized a protein of approximately 43 kDa on Western blot analysis in both membrane (soluble and nonsoluble) and cytosolic fractions of myometrium on each day of gestation. Expression of FP protein increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…Our findings of increased expression of mRNA for FP receptor and Cx-43 levels during uterine activation are consistent with the data from others in mouse (11), rat (1,35), and human myometrium (7,18,50). However, there is no direct evidence linking regulation of these genes with cytokine stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of increased expression of mRNA for FP receptor and Cx-43 levels during uterine activation are consistent with the data from others in mouse (11), rat (1,35), and human myometrium (7,18,50). However, there is no direct evidence linking regulation of these genes with cytokine stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…During late gestation, OT receptors (OTR) and prostaglandin F receptors (FP) are significantly induced in the myometrium in many mammalian species (Challis and Lye, 1994;Zingg et al, 1995;Imamura et al, 2000;Al-Matubsi et al, 2001; Arosh , 2004). In rats, the gestational profiles of the expressed Fos gene showed significantly higher transcript levels only during labour (Piersanti and Lye, 1995;Mitchell and Lye, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…mRNA levels for other coregulators (steroid receptor RNA activator, nuclear receptor corepressor, silencing mediator for retinoid and thyroid hormone receptor, Alien, and RIP-140) (10)(11)(12) and proteins that facilitate PR DNA binding (highmobility group proteins 1 and 2) (13) were variable, with no obvious trend between the in-labor and not-in-labor samples (data not shown). It has previously been reported that CnX43, OTR, and PGF 2␣ R are expressed in pregnant myometrium and increase with the onset of labor (14)(15)(16). To confirm at the molecular level that the myometrial tissues were classified correctly with regard to ''labor'' status, mRNA levels for the gap junction protein, CnX43, the OTR, and PGF 2␣ R were analyzed by using semiquantitative RT-PCR.…”
Section: Src-2 and -3 And Cbp Mrna Levels Are Significantly Reduced Imentioning
confidence: 99%